Different De Novo Initiation Strategies Are Used by Influenza Virus RNA Polymerase on Its cRNA and Viral RNA Promoters during Viral RNA Replication - Deng, Tao (American Society for Microbiology, 2006)
Various mechanisms are used by single-stranded RNA viruses to initiate and control their replication via the synthesis of replicative intermediates. In general, the same virus-encoded polymerase is responsible for both genome and antigenome strand synthesis from two different, although related promoters. Here we aimed to elucidate the mechanism of initiation of replication by influenza virus RNA polymerase and establish whether initiation of cRNA and viral RNA (vRNA) differed. To do this, two in vitro replication assays, which generated transcripts that had 5′ triphosphate end groups characteristic of authentic replication products, were developed. Surprisingly, mutagenesis screening suggested that the polymerase initiated pppApG synthesis internally on the model cRNA promoter, whereas it initiated pppApG synthesis terminally on the model vRNA promoter. The internally synthesized pppApG could subsequently be used as a primer to realign, by base pairing, to the terminal residues of both the model cRNA and vRNA promoters. In vivo evidence, based on the correction of a mutated or deleted residue 1 of a cRNA chloramphenicol acetyltransferase reporter construct, supported this internal initiation and realignment model. Thus, influenza virus RNA polymerase uses different initiation strategies on its cRNA and vRNA promoters. To our knowledge, this is novel and has not previously been described for any viral RNA-dependent RNA polymerase. Such a mechanism may have evolved to maintain genome integrity and to control the level of replicative intermediates in infected cells.